2017
DOI: 10.1016/j.ssmph.2017.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of a novel participatory multi-sector continuous improvement approach to enhance food security in remote Indigenous Australian communities

Abstract: BackgroundFood insecurity underlies and compounds many of the development issues faced by remote Indigenous communities in Australia. Multi-sector approaches offer promise to improve food security. We assessed the feasibility of a novel multi-sector approach to enhance community food security in remote Indigenous Australia.MethodA longitudinal comparative multi-site case study, the Good Food Systems Good Food for All Project, was conducted (2009–2013) with four Aboriginal communities. Continuous improvement me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
71
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(72 citation statements)
references
References 25 publications
1
71
0
Order By: Relevance
“…This review includes 12 cohort studies, 1 cohort39 with a ‘nested’ repeat cross-sectional study,44 2 repeat cross-sectional,40 54 2 interrupted time series,55 56 four case series53 57–59 and one each of retrospective pre–post study,60 multisite case study,61 non-randomised controlled study,37 stepped-wedge randomised controlled trial36 and an interrupted time series with a control group38 and a ‘nested’ cohort 45…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This review includes 12 cohort studies, 1 cohort39 with a ‘nested’ repeat cross-sectional study,44 2 repeat cross-sectional,40 54 2 interrupted time series,55 56 four case series53 57–59 and one each of retrospective pre–post study,60 multisite case study,61 non-randomised controlled study,37 stepped-wedge randomised controlled trial36 and an interrupted time series with a control group38 and a ‘nested’ cohort 45…”
Section: Resultsmentioning
confidence: 99%
“…Five studies (nine articles) described this intervention type 38–40 44 45 45 50 54 61. Two studies were assessed as cross-sectional40 50 54; one an interrupted time series with a control group38 (included a ‘nested’ cohort design)45; one a multisite case study61; and one a cohort39 (included a ‘nested’ cross-sectional design) 44. All were assessed as weak quality with two38 40 including additional impact evaluations both assessed as moderate 45 50.…”
Section: Resultsmentioning
confidence: 99%
“…Nutrition education including cooking skills workshops, group education sessions and store interventions have been reported to have some positive effect on obesity in Indigenous communities according to a review study that included both remote and urban communities in Australia 41. Multisector participatory approaches to strengthen food systems in remote Indigenous communities are needed42 with a special focus on nutrition in the early life.…”
Section: Discussionmentioning
confidence: 99%
“…72 73 Harness the food supply chain and action across sectors to ensure coherence with health Six studies evaluated multisectoral interventions aimed at improving food and/or beverage supply chains. [90][91][92][93][94][95] Evidence from Australian remote Indigenous communities suggests community-driven and multisectoral collaboration to improve local food systems, supply chains and environments, can increase sales of fruit, vegetables and water and reduce sales of confectionary and sugarsweetened beverages. 91 92 94 95 Furthermore, the two North American studies demonstrated harnessing Indigenous and non-Indigenous food systems to deliver healthy food directly to community settings, such as schools or community centres, can increase intake of healthy foods (including traditional foods) and reduce food insecurity among Indigenous Peoples.…”
Section: Bmj Global Healthmentioning
confidence: 99%